2010
DOI: 10.1002/14651858.cd003974.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Placebo interventions for all clinical conditions

Abstract: We did not find that placebo interventions have important clinical effects in general. However, in certain settings placebo interventions can influence patient-reported outcomes, especially pain and nausea, though it is difficult to distinguish patient-reported effects of placebo from biased reporting. The effect on pain varied, even among trials with low risk of bias, from negligible to clinically important. Variations in the effect of placebo were partly explained by variations in how trials were conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(220 citation statements)
references
References 367 publications
8
201
2
3
Order By: Relevance
“…While effect sizes remained similar to those in the first analysis, effects of placebo interventions over no treatment are now statistically significant for both patient-and observer-reported continuous outcomes and for binary outcomes owing to the larger number of included trials. While the evidence that there are placebo effects is stronger now, the authors still conclude that they 'did not find that placebo interventions have important clinical effects in general', as the overall effect size is small and the influence of bias unclear [40].…”
Section: What Is a Placebo Intervention In Clinical Practice?mentioning
confidence: 98%
See 1 more Smart Citation
“…While effect sizes remained similar to those in the first analysis, effects of placebo interventions over no treatment are now statistically significant for both patient-and observer-reported continuous outcomes and for binary outcomes owing to the larger number of included trials. While the evidence that there are placebo effects is stronger now, the authors still conclude that they 'did not find that placebo interventions have important clinical effects in general', as the overall effect size is small and the influence of bias unclear [40].…”
Section: What Is a Placebo Intervention In Clinical Practice?mentioning
confidence: 98%
“…Hró bjartsson & Gøtzsche published updated and expanded versions of their review in 2004 [39] and 2010 [40]. The current analysis now includes 202 trials.…”
Section: What Is a Placebo Intervention In Clinical Practice?mentioning
confidence: 99%
“…A systematic review of clinical trials was conducted in which patients were randomly assigned to either placebo or no treatment [28][29][30]. The authors' goal was to study the clinical significance of placebos by discerning whether patients randomized to placebo under blind conditions have better outcomes than those randomized to no treatment.…”
Section: Best Evidence Clinician Behaviours and Patient Attitudes Tomentioning
confidence: 99%
“…A meta-analysis published by the Cochrane Database of Systematic Reviews in 2004 (Hróbjartsson & Gøtzsche, 2004) reported no evidence for important clinical effects from placebo interventions. Just six years later a follow-up meta-analysis (Hróbjartsson & Gøtzsche, 2010) found sufficient evidence to support the use of placebo as an effective treatment for pain.…”
Section: International Journal Of Transpersonal Studies 133 Placebo Rmentioning
confidence: 99%